The impact of COVID-19 pandemic on TVET students’ learning process: A case of one Polytechnic College in Harare - Masina, R.; Mawonedzo, A. (South African Journal of Higher Education, 2022)
A series of transformations have taken place in the education system due to COVID-19 pandemic. This research is aimed at determining the impact of COVID-19 on the learning process with special reference to Technical Vocational Education and Training (TVET) students in Zimbabwe. A qualitative research approach was used involving a multiple case study research design. The study sample included two Clothing and Textile Technology (CTT), two Building Technology (BT), and two Food Technology (FT) students; and three lecturers at one selected Polytechnic College in Harare. Participants were purposively sampled. Data was collected through interviews with lecturers, focus group discussions with students and a review of uploaded materials. Thematic data analysis approach was used followed by a cross-case analysis of the three subject areas. The study established that the most affected subjects were CTT and BT. However, little effect was experienced in FT. The researchers therefore recommend a methodological shift from the traditional instructional designs to modern methods that address the prevailing conditions brought about by the pandemic. This requires all educational stakeholders’ ingenuity to institute feasible methods that would cater for all technical subjects in the transfer of the conventional educational systems to blended learning.